Creative Engagement: Multimodal digital games in children's learning environment in Macau S.A.R. - Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts, 2017)
One of the biggest challenges that we have encountered, when trying to encourage digital games in schools, is trying to explain what its benefits are in teaching and learning environments. In this pilot experimental study we explore how multimodal audio and visual games can be used in learning environments for children, specifically by fostering creative behaviors through User-Centered design approaches. To achieve this objective, a framework is being developed with multimodal experiences based on flexible design patterns that exploits basic visual and audio elements, allowing children from three to six years of age to play and learn through fun and subsequently trigger creative behaviors. These studies are making use of tangible objects, digital games and mobile platforms. We are making use of commercial digital games to understand and discuss the affordances of these games in an educational environment and how they support creativity in learning. (Fig.1)
Keywords: Children; Creative Learning; Devices; Digital Games; Mobile; Multimodal; Tangible Technologies; User-Centered Design

Sounding Architecture: Inter-Disciplinary Studio at HKU - Barbosa, Alvaro; Tsang, Thomas (Proceedings of the International Conference on New Interfaces for Musical Expression, 2017)
Sounding Architecture, is the first collaborative teaching development between Department of Architecture and Department of Music at the University of Hong Kong (HKU), introduced in Fall 2016. In this paper we present critical observations about the studio after a final public presentation of all projects. The Review was conducted with demonstrations by groups of students supervised by different Lecturer, in each case focusing on a different strategy to create a connection between Sound, Music, Acoustics, Space and Architectural Design. There was an assumption that the core working process would have to include the design of a new musical instrument, which in some cases became the final deliverable of the Studio and in other cases a step in a process that leads to a different outcome (such as an architectural Design, a performance or social experiment). One other relevant aspect was that Digital technology was used in the design and fabrication of the physical instruments' prototypes, but in very few cases, it was used in the actual generation or enhancement of sound, with the instruments relying almost exclusively in acoustic and mechanical sound.
GSCC: 0000000

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts (ARTECH 217), 2017)
0 citations (Crossref) [2022-09-21] GSCC: 0000000